Pendampingan Penerapan Model Pelayanan yang Memuaskan Pegawai dan Masyarakat Berbasis Total Quality Management - Dasman Lanin; Boni Saputra; Lince Magriasti; Afifah Asriati; Beta Santria Sholehah; Muhammad Nasrullah (Universitas Lancang Kuning, 2022)
The purpose of service is to assist in improving the understanding and skills of Nagari employees in implementing a service model that satisfies the community and Nagari employees, then innovating and developing excellent problem solver skills. The Nagari government is required to be independent in this regard. The village where this service is located is Suayan, Akabiluru District, Fifty Cities Regency, this village has not been able to manage good or excellent services. This Nagari still does not have a service recording machine that is connected online. While Nagari is the government closest to the people. This service activity is ultimately able to provide skills in utilizing service recording machines, as well as being skilled at detecting the weaknesses of nine indicators that are not yet prime (Menpan RB). This service activity is carried out using participatory and mentoring methods. The results achieved are (1) there has been a shift in orientation from a bureaucratic orientation to a public orientation among employees. The ability to understand the TQM-based service model has increased, (2) the skills of Nagari employees have increased, in carrying out services for the satisfaction of the Nagari community. Henceforth, it must be accompanied by a service machine that is connected to a computer (e-government). as well as intensive discussions to become skilled Problem Solvers towards truly excellent service.